Implementation of Green Human Resource Management in Jatiluwih Tourism Destination Area - Gst Nym Suci Murni, Ni; Nyoman Winia, I; Wayan Pugra, I; Made Darma Oka, I (Riviera Publishing, 2023)
Jatiluwih tourism destination is one of the World Cultural Heritage Areas of Catur Angga Batukaru, included in the Balinese Cultural Landscape set by UNESCO in 2012. This tourist village needs to be supported by green human resource management as a sustainable destination. Therefore, this research aims to examine green human resource management (GHRM) implementation to design a suitable model and support sustainable tourism. It uses a qualitative descriptive analysis backed by quantitative data. Furthermore, data were collected through observation, in-depth interviews, documentation, focus group discussions, and questionnaires to all sub-village (sub-village) communities. Informants were selected from community leaders, namely the village head (perbekel), the head of destination management, the head of the LPM, and representatives from 9 divisions of the Jatiluwih destination management. The research discussion was analyzed using Miles & Huberman analysis, involving data reduction, display, verification, and conclusion. The results showed that the GHRM in Jatiluwih destination was well implemented under observations, interviews, and questionnaires. However, for the sustainability of future management under the results of the focus group discussions conducted with community leaders and managers, it is necessary to design a suitable GHRM model for the Jatiluwih tourist village. It can also be used as a model to manage similar tourist villages in other areas. GHRM has been appropriately implemented, as evidenced by the results of interviews, and focus group discussions (FGD) conducted with the managers of the Jatiluwih destination.